Variations in Antibiotic and Azithromycin Prescribing for Children by Geography and Specialty—United States, 2013. Issue 1 (January 2018) - Fleming-Dutra, Katherine E.; Demirjian, Alicia; Bartoces, Monina; Roberts, Rebecca M.; Taylor, Thomas H.; Hicks, Lauri A.
Abstract : Background: Using antibiotics appropriately is critical to slow spread of antibiotic resistance, a major public health problem. Children, especially young children, receive more antibiotics than other age groups. Our objective was to describe antibiotic use in children in the United States and use of azithromycin, which is recommended infrequently for pediatric conditions. Methods: We used QuintilesIMS Xponent 2013 data to calculate the number and rate of oral antibiotic prescriptions for children by age (0–2, 3–9 and 10–19 years) and agent. We used log-binomial regression to calculate adjusted prevalence ratios and 95% confidence intervals to determine if specialty and patient age were associated with azithromycin selection when an antibiotic was prescribed. Results: In 2013, 66.8 million antibiotics were prescribed to US children ⩽19 years of age (813 antibiotic prescriptions per 1000 children). Amoxicillin and azithromycin were the 2 most commonly prescribed agents (23.1 million courses, 35% of all antibiotics; 12.2 million, 18%, respectively). Most antibiotics for children were prescribed by pediatricians (39%) and family practitioners (15%). Family practitioners were more likely to select azithromycin when an antibiotic was prescribed in all age groups than pediatricians (for children 0–2 years of age: prevalence ratio: 1.79, 95% confidence interval: 1.78–1.80; 3–9 years: 1.40, 1.40–1.40 and 10–19 years: 1.18, 1.18–1.18). Conclusion: Despite infrequent pediatric recommendations, variations in pediatric azithromycin use may suggest inappropriate antibiotic selection. Public health interventions focused on improving antibiotic selection in children as well as reducing antibiotic overuse are needed. Abstract : Supplemental Digital Content is available in the text.